Moral and Justice as the Philosophical Basis of Legal Education: A Criticism of the Indonesian Ministry of Education's “Merdeka Belajar” and “Kampus Merdeka” Concepts - Ridwan, Ridwan; Achmadi, Achmadi; Budiono, Arief; Sholahuddin Al Fatih; Rahmatullah Ayu Hasmiati; Iriani, Dewi (Տիգրան Մեծ)
The Indonesian Ministry of Education and Culture has applied the „Merdeka Belajar‟ (Freedom to Learn) and „Kampus Merdeka' (The Freedom Campus) (abbreviated MBKM) learning concepts. In legal education, these concepts aim to form legal students who master the knowledge, skills, and competence demanded by the job market. Unfortunately, these programs lack the fundamental vision to create honest individuals of law that have integrity. This paper analyzed the MBKM program that only envisions catering students to the needs of the job market and how that policy neglects the essence of legal education, namely morals and justice. This re-search employs the philosophical approach. Without morality, the legal sector will become a facility for destruction through moral hazards such as corruption, collusion, and manipulation. A legal expert should ideally strive to demand and up-hold justice, truth, goodness, and virtue, as well as the integrated and personal moral ideals that are non-existent in the MBKM concept. The MBKM policy in legal education needs to be revised as legal education should emphasize its philosophical essence; namely the perspective of justice can only be achieved through moral integrity. Contribution of completed study to modern education to remind, the philosophical essence is still needed.
Keywords: Philosophy; Philosophy of education